Atypical course of type 1 diabetes mellitus in a patient with Ollier’s disease - a case report - Kochanowska, Anna; Knop, Kinga; Piasecka, Zuzanna; Kowalczuk, Maria; Rudzki, Grzegorz (Journal of Education, Health and Sport, 2022)
Background Nowadays, we can distinguish more than two types of diabetes mellitus. Due to blood glucose measurement and genetic tests, different types of diabetes (such as autoimmune, monogenetic, atypical) can be detected. Despite the constantly updated recommendations and the progress of diagnostic tests, making a diagnosis may be difficult. Case report A 23-year old patient was admitted to the Department of Endocrinology due to diagnosed diabetes mellitus to determine its primary cause. Elevated blood glucose level was identified during periodic medical test and was confirmed by OGTT test. In the patient’s medical history: Ollier’s disease with multiple enchondromas, treated surgically in childhood, no typical symptoms and risk factors of hyperglycaemia. During hospitalization the laboratory tests showed decreased level of C-peptide, nevertheless the patient represented acceptable levels of glycaemia following only by diet restriction. MODY, LADA and diabetes due to Ollier’s disease was speculated. Due to suspicion of autoimmunological cause the diagnostic was extended by testing antibodies: IAA, IA2, GAD, IC, which confirmation allowed to recognise untypical diabetes mellitus type 1. The patient objected to insulin treatment, limited it only to a diet and maintained normoglycemia for 15months. However, after an increase in glycaemia and in HbA1c, insulin therapy was introduced. Disscussion with conclusion Atypical course of diabetes should be considered in patients with a known disorder or with comorbidities associated with diabetes and without typical symptoms of hyperglycaemia. Atypical forms of diabetes are uncommon and require etiology-specific therapies.